How novel actors achieve a positive reputation: A case of prep schools with elite-level hockey programs - Washington, M.; Edwards, J. (Canadian Journal of Administrative Sciences, 2018)
How are novel organizations able to build a positive reputation while attempting to enter into a system with established organizations? To address this, we examined the field of elite-level amateur hockey. Private Secondary Schools (PSS) are novel in that they offer a nontraditional pathway for players with respect to fielding elite-level hockey teams. Findings from interviews with PSS with elite-level hockey programs revealed that PSS highlight their Selection Processes, Player Development Practices, and the enhanced Player Experience in an effort to build a positive reputation. This study contributes to the literature on reputation by showing that novel organizations can build a reputation through highlighting the unique value they add